Heat Transfer Behaviour Inside a Sinusoidal Cavity Using Water Based Tio2 Nanofluid - Saha, Goutam (GANIT: Journal of Bangladesh Mathematical Society, 2018)
A numerical investigation is carried out to observe the augmentation of heat transfer because of the presence of TiO2 nanofluid inside a sinusoidal cavity. In this study, upper and lower walls of the cavity are considered adiabatic, higher and lower temperature are maintained at left and right vertical walls respectively. Also, 2D contour of velocity and temperature with average heat transfer rate are presented and discussed. Our findings show that augmentation of heat transfer is feasible with the increase of concentrations of nanoparticles. GANIT J. Bangladesh Math. Soc.Vol. 37 (2017) 121-129